2020
DOI: 10.3847/2041-8213/ab62b8
|View full text |Cite
|
Sign up to set email alerts
|

GeV–TeV Counterparts of SS 433/W50 from Fermi-LAT and HAWC Observations

Abstract: The extended jets of the microquasar SS 433 have been observed in optical, radio, X-ray, and recently very-high-energy (VHE) γ-rays by HAWC. The detection of HAWC γ-rays with energies as great as 25 TeV motivates searches for high-energy γ-ray counterparts in the Fermi-LAT data in the 100 MeV-300 GeV band. In this paper, we report on the first-ever joint analysis of Fermi-LAT and HAWC observations to study the spectrum and location of γ-ray emission from SS 433. Our analysis finds common emission sites of GeV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…This may indicate the magnetic field is weak or the radio continuum emission tracing the magnetic field already disappeared by synchrotron radiation. The GeV gamma-ray emission has recently been detected toward the jet from SS433 (Abeysekara et al 2018;Fang et al 2020;. N4 is located at the edge of the distribution of the gamma-ray emission.…”
Section: Comparison With High Energy Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…This may indicate the magnetic field is weak or the radio continuum emission tracing the magnetic field already disappeared by synchrotron radiation. The GeV gamma-ray emission has recently been detected toward the jet from SS433 (Abeysekara et al 2018;Fang et al 2020;. N4 is located at the edge of the distribution of the gamma-ray emission.…”
Section: Comparison With High Energy Radiationmentioning
confidence: 99%
“…There gamma-ray radiation up to TeV was detected, and the origin of the TeV gamma-ray was discussed to result from the interaction of high energy cosmic-ray proton with an interstellar proton. Various gamma-ray observations have been conducted toward the SS433/W50 system (e.g., Abeysekara et al 2018;Fang et al 2020). Actually, toward the jet from SS433, Gev-TeV gamma-ray have been detected, and their origins have been discussed…”
Section: Comparison With High Energy Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that Q e ∝ E −2 e up to a maximum energy E e,max = 3 PeV and source emission time ∼ 0.1 Myr (just for demonstrative purposes), we find that the total electron power L e = Ee,max mec 2 ∼ 10 37 (d/5 kpc) 2 erg s −1 is sufficient to explain the Tibet ASγ flux, where d is the average source distance. Although the mechanism of PeV electron acceleration remains an open question, leptonic sources with such hard spectra and high E e,max have been previously observed (see, e.g., HAWC Collaboration et al 2018Collaboration et al , 2019Fang et al 2020).…”
Section: Leptonic Sourcesmentioning
confidence: 99%
“…Recently, Fang et al (2020) performed a joint analysis of LAT and HAWC data, and concluded that the GeV gamma-ray data may be smoothly connected to the TeV range with a photon index Γ ∼ 2.1. They found that the previous LAT analyses were affected by nearby sources, J1913.3+0515 in the LAT 8-year point source catalog and J1907.9 + 0602 in the 4FGL catalog (The Fermi-LAT collaboration 2019).…”
Section: Introductionmentioning
confidence: 99%